Use of Nanocoatings in Textiles for Sportwear - Quiroga Barreto, Angélica Margoth
The sports apparel industry is experiencing a boom thanks to the growing awareness of health and well-being, which hasdriven the demand for specialized garments. This ongoing growth and investment in research and material developmentpromise to continue transforming the way sports performance is assessed in the future, along with the utilization of emergingtechnologies in the fashion system. Desirable properties in sports apparel include breathability, elasticity, water resistance,lightweightness, durability, UV protection, compression, and antibacterial properties. Each of these properties plays a crucialrole in the athlete’s performance and comfort during physical activity. The incorporation of nanotechnology into fabrics hassparked significant interest due to its unique characteristics and potential benefits compared to traditional coatings. In thisresearch, the latest advancements in the application of nanocoatings in textiles for sports apparel are unveiled, utilizingsilica and titanium nanoparticle-based coatings to impart hydrophobicity and UV protection.